2012
DOI: 10.1590/s0004-282x2012000300003
|View full text |Cite
|
Sign up to set email alerts
|

Use of psychotropic medications by caregivers of elderly patients with dementia: is this a sign of caregiver burden?

Abstract: This study evaluated the consumption of psychotropic medications by caregivers of elderly patients with or without dementia. This was a cross-sectional study conducted at all geriatric units in Brasília, Brazil, during a two-month period. Structured interviews were performed with 311 caregivers of people with or without dementia and they completed questionnaires. Among the caregivers, 196 (63%) were caregivers of patients with dementia and 115 (37%) were caregivers of patients without dementia. Forty-four care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 19 publications
0
12
0
6
Order By: Relevance
“…Such data are corroborated by other studies, which show, in addition to more women providing care for dependent older people, a mean age similar to our findings. 13,14 With regard to QOL of caregivers, the environmental domain was correlated with the perception of daily safety. By analyzing the QOL of caregivers of elderly individuals with hearing impairments in light of the WHOQOL-BREF, a study conducted in the state of Rio Grande do Sul, in Brazil, found the environment and physical domains were the most related and more closely involved with QOL of caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Such data are corroborated by other studies, which show, in addition to more women providing care for dependent older people, a mean age similar to our findings. 13,14 With regard to QOL of caregivers, the environmental domain was correlated with the perception of daily safety. By analyzing the QOL of caregivers of elderly individuals with hearing impairments in light of the WHOQOL-BREF, a study conducted in the state of Rio Grande do Sul, in Brazil, found the environment and physical domains were the most related and more closely involved with QOL of caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Dementia caregivers who experience high burden have high rates of depression (Epstein-Lubow, Davis, Miller, & Tremont, 2008), higher utilization of health services (Draper, Poulos, Cole, Poulos, & Ehrlich, 1992; Kiecolt-Glaser, Dura, Speicher, Trask, & Glaser, 1991; Schubert et al, 2008), higher use of psychotropic medications (Camargos et al, 2012; Pérodeau, Lauzon, Lévesque, & Lachance, 2001), and greater 4-year mortality than noncaregivers (Schulz & Beach, 1999). …”
Section: Introductionmentioning
confidence: 99%
“…16 Stress accruing from delivering care affects various health dimensions of caregivers, including self-perception of health 17 and the use of medica-tion. 18 One study shows that caregivers experience an increase in negative symptoms by one third after assuming the responsibility of providing care. Additionally, spouse caregivers also report an increase in infectious diseases, especially those in the upper respiratory tract.…”
Section: Discussionmentioning
confidence: 99%